2y-4=-3y

Simple and best practice solution for 2y-4=-3y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2y-4=-3y equation:


Simplifying
2y + -4 = -3y

Reorder the terms:
-4 + 2y = -3y

Solving
-4 + 2y = -3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '3y' to each side of the equation.
-4 + 2y + 3y = -3y + 3y

Combine like terms: 2y + 3y = 5y
-4 + 5y = -3y + 3y

Combine like terms: -3y + 3y = 0
-4 + 5y = 0

Add '4' to each side of the equation.
-4 + 4 + 5y = 0 + 4

Combine like terms: -4 + 4 = 0
0 + 5y = 0 + 4
5y = 0 + 4

Combine like terms: 0 + 4 = 4
5y = 4

Divide each side by '5'.
y = 0.8

Simplifying
y = 0.8

See similar equations:

| M/0.4=0.3 | | 87,187,500+175,000= | | 60/4x | | n+(n+175000)=625,000,000 | | 3x+1+6=5x+8-2x | | n+(n+20)=334 | | 4x-28=3x+21 | | 5+2x/6+x | | (25-13)/4*2= | | 2x3/2=16 | | 0.02(x+200)=0.72 | | 2-0.75= | | 2x^2+8x-27=0 | | 3x+16+68=90 | | 3+14t-1=9t+9-2t | | 9x-5-3x+10=46 | | 3.4=13.6+(3.4c)1.7c | | 47-4x=5x+18 | | 5+10y=3y-4 | | y=3x+-42 | | y=88-11 | | 1.5(x-4)=.75(2x-7) | | 3(x+9)=5x+11 | | (3-5i)(2+9i)+(7+2i)(7-2i)=0 | | 24x^2+4x^3+32x=0 | | 5(3-4m)=35 | | x+5+11/4=180 | | 24-x=3x+4 | | -4(3b+2)+(13b-1)=0 | | (36x-20y)+(39x+55y)= | | (14x+5y)+(44x+34y)= | | (15x+6y)+(41x+34y)= |

Equations solver categories